1979
DOI: 10.1037/0033-2909.86.6.1201
|View full text |Cite
|
Sign up to set email alerts
|

Superior–subordinate communication: The state of the art.

Abstract: Based on a review of the literature, empirical research in the area of superiorsubordinate communication is classified into nine topical categories and critically examined. Inspection of this literature suggests that researchers have focused the majority of their attention on studying (a) the effects of power and status on superior-subordinate communication, (b) trust as a moderator of superior-subordinate communication, and (c) semantic-information distance as a source of misunderstanding in superior-subordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
137
0
6

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(151 citation statements)
references
References 158 publications
8
137
0
6
Order By: Relevance
“…Therefore, given the importance of the role of communication in leadership, it is not surprising that a great deal of attention has been paid to the search for a common communication style among effective leaders (Jablin, 1979). Interpersonal leader-subordinate communication is one of the major areas of organisational communication and proper communication and understanding must be clearly denoted between leaders and subordinates (Schwandt & Marquardt, 2000a).…”
Section: Supervisor-subordinate Communication and Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, given the importance of the role of communication in leadership, it is not surprising that a great deal of attention has been paid to the search for a common communication style among effective leaders (Jablin, 1979). Interpersonal leader-subordinate communication is one of the major areas of organisational communication and proper communication and understanding must be clearly denoted between leaders and subordinates (Schwandt & Marquardt, 2000a).…”
Section: Supervisor-subordinate Communication and Leadershipmentioning
confidence: 99%
“…They believe that leaders with high levels of consideration are more likely to be concerned about interpersonal relations and emphasizing communication with subordinates than leaders who follow initiating structural style (Jablin, 1979;Redding, 1972). In fact, communication between management and staff should be reciprocal and "two-way," and therefore building more "two-way" communication and involvement by the members will result in greater support from management (McCabe & Garavan, 2008).…”
Section: Supervisor-subordinate Communication and Leadershipmentioning
confidence: 99%
“…For instance, researchers explored the role and efficiency of information routing in centralized and hierarchical networks as opposed to more decentralized networks (Jablin, 1979(Jablin, , 1987Leavitt, 1951;Mackenzie, 1976;Shaw, 1964Shaw, , 1978. It was found that as soon as tasks become more complex and multifaceted, groups tend to gravitate naturally to more decentralized networks (Brown & Miller, 2000;Shaw, 1978).…”
Section: Internal Models Of Sourcesmentioning
confidence: 99%
“…Sehubungan itu, kajian ini dilakukan bertujuan untuk meneliti implikasi perbezaan faktor demografi terhadap pemboleh ubah lain yang terdapat dalam organisasi iaitu Jabatan Penjara. PERBEZAAN (Jablin 1979). Kajian-kajian terkini berkaitan dengan kesan kepelbagaian demografi masih menunjukkan bukti yang tidak meyakinkan (Joshi, Liao & Roh 2011).…”
Section: Latar Belakang Kajianunclassified